2018
DOI: 10.3390/su10020504
|View full text |Cite
|
Sign up to set email alerts
|

Peace with Hunger: Colombia’s Checkered Experience with Post-Conflict Sustainable Community Development in Emerald-Mining Regions

Abstract: Abstract:The interactions between conflict and local development has puzzled scholars and practitioners alike. This article explores why the advent of peace in Colombia's emerald-mining regions for the past few years, as well as a broader national peace process, has not delivered the expected development dividends among mining communities. We contrast differences in stakeholders' perceptions between levels of governance (local, regional and national). Based on the research, we conclude that while stakeholder c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The case study of the brownfields in Karvina, Czech Republic found that awareness about problems connected to brownfields is quite limited [18]. A study conducted in Colombia recommended the preparation and better coordination of stakeholders in order to engage complex relationships and protect community assets in a collaborative governance scenario [19]. The policy of selected leaders in the mining industry in Poland is an example of promoting good practices within the corporate responsibility of enterprises.…”
Section: Introductionmentioning
confidence: 99%
“…The case study of the brownfields in Karvina, Czech Republic found that awareness about problems connected to brownfields is quite limited [18]. A study conducted in Colombia recommended the preparation and better coordination of stakeholders in order to engage complex relationships and protect community assets in a collaborative governance scenario [19]. The policy of selected leaders in the mining industry in Poland is an example of promoting good practices within the corporate responsibility of enterprises.…”
Section: Introductionmentioning
confidence: 99%
“…Natural resource benefits continue to accrue to a "few hands, leading to a deterioration in many aspects of community livelihoods and wealth distribution" (Franco and Ali 2016). In addition, as in the two case studies in this study, there is a trend of the shift of wealth from local people to local elites and from local elites to multinational corporations in many resource-rich regions (Franco et al 2018). These circumstances would require a real paradigm shift in the governance processes and the decentralization framework to contain local power brokers and level the playing field for all stakeholders.…”
Section: Decentralization Resource Use and Resource Managementmentioning
confidence: 73%
“…Local governments are expected to balance the preferences of local communities with national goals and provide those communities with greater influence in decision-making, but this has not occurred in most places (Franco et al 2018). Decentralization outcomes may often appear successful as perceived from a top-down lens in government but not at local levels (Franco et al 2018). Natural resource benefits continue to accrue to a "few hands, leading to a deterioration in many aspects of community livelihoods and wealth distribution" (Franco and Ali 2016).…”
Section: Decentralization Resource Use and Resource Managementmentioning
confidence: 99%
“…Since the extensive public security expenditure also affects employment and other economic sectors, any demilitarisation processes would need to be coupled with alternative opportunities for employment and income. Unemployment reduces the opportunity costs of starting a conflict [21], and the lack of employment opportunities can exacerbate the community situation and maintain any conflict [41], both conditions which are relevant to the Algerian case.…”
Section: The Economic Outlook In Algeriamentioning
confidence: 99%
“…Additionally, there was a slight increase in oil and natural gas production after the civil war (Figures 7 and 8). Unemployment reduces the opportunity costs of starting a conflict [21], and the lack of employment opportunities can exacerbate the community situation and maintain any conflict [41], both conditions which are relevant to the Algerian case.…”
Section: The Economic Outlook In Algeriamentioning
confidence: 99%